CONTRIBUTION OF THE RUGBY TAG GAME TO DEVELOPING MOTRIC SKILLS, SPEED AND ABILITIES IN STUDENTS OF THE GYMNASIAL CYCLE - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The main objective of the research that we have chosen is to find some strategies that will allow us to improve the indicators of motric qualities - speed and ability. Being a passionate rugby player, in order to fulfill the objective, I have carefully selected specific methods that have the effect of improving these qualities. In school, during the physical education lesson, a variant of the rugby game is Srugby or Rugby-tag where there is no direct contact with the opponent.